Validity and Reliability of Motivation and Stress on Employee Performance - Hartati Hartati; Andi Novi; Megawati Beddu (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2020)
This research aims to reveal the influence of motivation and job stress on employee performance at PT Makassar Raya Motor (Daihatsu) Parepare. The research method used in measuring the effectiveness of employee performance is the saturation sampling method. Then motivation and job stress become independent variables in improving employee performance so that, this research describes a discussion of motivation and job stress. The research results show that both motivation and job stress have a significant and significant effect on employee performance at PT Makassar Raya Motor. One sample from the object of research in this article, namely PT Makassar Raya Motor, which is a Daihatsu car dealer, is required to increase its ability to face competition. One way to increase abilities is to pay attention to the motivation and stress factors of the workforce, in this case, the employees of the marketing division.